2006
DOI: 10.1007/s10038-006-0385-6
|View full text |Cite
|
Sign up to set email alerts
|

A −16C>T substitution in the 5′ UTR of the puratrophin-1 gene is prevalent in autosomal dominant cerebellar ataxia in Nagano

Abstract: The molecular bases of autosomal dominant cerebellar ataxia (ADCA) have been increasingly elucidated, but 17-50% of ADCA families still remain genetically undefined in Japan. In this study we investigated 67 genetically undefined ADCA families from the Nagano prefecture, and found that 63 patients from 51 families possessed the )16C>T change in the puratrophin-1 gene, which was recently found to be pathogenic for 16q22-linked ADCA. Most patients shared a common haplotype around the puratrophin-1 gene. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 26 publications
(39 reference statements)
1
43
1
Order By: Relevance
“…Thus, an accumulation of 16q-linked ADCA families leads to a moderately high prevalence of SCD in Hokkaido. 16q-linked ADCA was also very prevalent in ADCA families in the Nagano districts of Japan (Ohata et al 2006). Table 2 summarizes the high prevalence of 16q-linked ADCA in various localities throughout Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an accumulation of 16q-linked ADCA families leads to a moderately high prevalence of SCD in Hokkaido. 16q-linked ADCA was also very prevalent in ADCA families in the Nagano districts of Japan (Ohata et al 2006). Table 2 summarizes the high prevalence of 16q-linked ADCA in various localities throughout Japan.…”
Section: Discussionmentioning
confidence: 99%
“…This substitution was also found in other cohorts of Japanese families with ataxia (Ouyang et al 2006;Onodera et al 2006), while it was not found in Caucasian patients in Europe (Wieczorek et al 2006). The frequency of 16q-ADCA is considered to be relatively high in Japan, counted as the third or fourth major subtype of ADCA after MJD, SCA6, and DRPLA (Takano et al 1998;Sasaki et al 2003;Ohata et al 2006).…”
Section: Introductionmentioning
confidence: 53%
“…Family U09 and the family reported by Ohata et al 2006) also suggested ancestral chromosomal recombination around the substitution in the puratrophin-1 gene. Therefore, we searched the SNPs around these four markers and the puratrophin-1 gene.…”
Section: Haplotype Analysis With Snpsmentioning
confidence: 77%
See 2 more Smart Citations